2023
DOI: 10.3390/ijms24065368
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status and Psoriatic Arthritis: Association with the Risk for Sacroiliitis and Influence on the Retention Rate of Methotrexate Monotherapy and First Biological Drug Survival—A Retrospective Study

Abstract: A growing body of evidence on the importance of vitamin D in immune modulation has increased the interest in its possible impact on the course of rheumatological diseases. The scope of our study is to assess if the presence of different statuses of vitamin D could interfere in the clinical subsets, in methotrexate monotherapy discontinuation, and biological drug (b-DMARDs) survival in psoriatic arthritis patients (PsA). We conducted a retrospective study on PsA patients and split them into three groups based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…In harmony, Rotondo et al 26 noted a high frequency of axial affection in the psoriatic patients with vitamin D deficiency which go hand by hand with Fernandes et al 27 who considered presence of axial affection as indicator of disease severity. 28 noticed that vitamin D level was significantly linked to the functional ability in psoriatic arthritis that supports our findings.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In harmony, Rotondo et al 26 noted a high frequency of axial affection in the psoriatic patients with vitamin D deficiency which go hand by hand with Fernandes et al 27 who considered presence of axial affection as indicator of disease severity. 28 noticed that vitamin D level was significantly linked to the functional ability in psoriatic arthritis that supports our findings.…”
Section: Discussionmentioning
confidence: 96%
“…On the contrary, Rotondo et al 26 showed that vitamin D level was not correlated with inflammatory markers, furthermore, Ibrahim et al 19 and Sag˘et al 25 reported that vitamin D level was not correlated with CRP.…”
Section: Montolio-chiva Etmentioning
confidence: 97%
“…In a retrospective study involving 233 PsA patients, 25(OH)D 3 ≤ 20 ng/dL has been associated with a higher discontinuation rate of both conventional disease-modifying antirheumatic drugs (cDMARD (methotrexate), p = 0.02) and first biological DMARDs (p = 0.02) when compared to 25(OH)D 3 > 20 ng/dL [16].…”
mentioning
confidence: 99%